Clinical and cytopathological characteristics of HTLV‐1+ hodgkin lymphoma. (28th June 2020) - Kobata, Katsumi; Kimura, Shoichi; Mihashi, Yasuhito; Iwasaki, Hiromi; Nonaka, Shuichi; Matsumoto, Shinji; Takamatsu, Yasushi; Choi, Ilseung; Kawauchi, Shigeto; Ishitsuka, Kenji; Takeshita, Morishige
Abstract: Background: Human T‐lymphotropic virus‐1 (HTLV‐1) + Hodgkin lymphoma (HL) is difficult to differentiate from adult T‐cell leukemia/lymphoma (ATLL) with HL‐like histology (HL‐like ATLL). Methods: Cytological and immunohistological features, HTLV‐1 proviral DNA integration, and rearrangements of the T‐cell receptor (TCR) Cβ1 gene were examined in 11 HTLV‐1 + patients with HL‐like disease. Results: Six patients were classified as HTLV‐1 + HL and five as HL‐like ATLL in accordance with genetic findings of HTLV‐1 proviral DNA integration and rearrangements of the TCR Cβ1 gene. Small ordinary looking lymphocytes with round nuclei were detected in the background of six patients with HTLV‐1 + HL, which were immunohistochemically negative for CD25 and CC chemokine receptor (CCR)4 and had a low MIB1 labeling index (mean: 28.3%). In the HL‐like ATLL specimens, small‐ and medium‐sized atypical lymphocytes with indented and irregular‐shaped nuclei were found, and were diffusely positive for CD25 and CCR4, with high MIB1 labeling (mean: 76%). Both groups had scattered CD30 + and CD15 + Hodgkin and Reed Sternberg (RS) giant cells, with or without CD20 expression and Epstein‐Barr virus infection. The 50% overall survival period was significantly longer for the HTLV‐1 + HL group (180 months) than for the HL‐like ATLL group (7.8 months; P  = .004). Conclusions: HTLV‐1 + HL showed typical small lymphoid cells with a low MIB1 labeling index in a background of Hodgkin and RS cells, with some scattered CD25 + and CCR4 + lymphocytes. In HTLV‐1 endemic areas, distinguishing HTLV‐1 + HL from HL‐like ATLL is important because of their differing treatment strategies and prognoses. Abstract : Human T‐lymphotropic virus‐1 (HTLV‐1) + Hodgkin lymphoma (HL) is difficult to differentiate from adult T‐cell leukemia/lymphoma with HL‐like histology. Here, we compared cytohistology, clinicopathological features and prognoses between patients with genetically confirmed HTLV‐1 + HL and those with HL‐like ATLL.